Development and characterization of honey-plga microparticles with antibacterial properties against streptococcus mutans in oral disease - Imm, Chu Liu (2023)
Application of honey in a certain area of the human body like in the oral cavity might pose a problem due to its liquidity. Thus, honey also has been explored to be used in other forms for suitable application. One form of drug delivery system is through the incorporation of drugs into microparticles. Therefore, the aim of this study is to investigate the potential of honey to be incorporated into microparticles to enhance antibacterial activity. Three types of honey were used; Kelulut, Tualang and Manuka. Honey-PLGA microparticles were prepared using the double emulsion solvent evaporation method. Then the honey-PLGA microparticles were subjected to a variety of analyses and tests, including GC-MS analysis, FESEM, zetasizer analysis, in vitro release and an antibacterial test. Streptococcus mutans was used for antibacterial testing because this bacterium causes caries and periodontitis. The results showed that all types of honey used in this study could be incorporated into microparticles as a white powder. Based on FESEM analysis, honey-PLGA microparticles were spherical, and had a smooth surface, with a diameter ranging from 1 to 10 micrometer. GC-MS analysis showed the identified compounds found in raw Kelulut honey microparticles (RKHMP), raw Manuka honey microparticles (RMHMP) and raw Tualang honey microparticles (RTHMP) were 1, 11 and 5 compounds, respectively. The identified compounds found in extracted Kelulut honey microparticles (EKHMP), extracted Manuka honey microparticles (EMHMP) and extracted Tualang honey microparticles (ETHMP) were 15, 12 and 26 compounds, respectively. Extracted honey microparticles contain more identified compounds compared to raw honey microparticles. Zetasizer analysis showed the microparticles had low zeta potential and thus tended to precipitate in suspension. The microparticles showed slow-release character but no antibacterial activity against Streptococcus mutans. Within the limitation of the study, it can be concluded that, the three types of honey can be incorporated with other materials to produce honey-PLGA microparticles, however further study is needed in term of improving the formulation to produce microparticles that are highly effective against target microorganisms.